OP26 Disentangling the role of HLA proteins in shaping the T-cell repertoire in Inflammatory Bowel Disease using CDR3-QTL analysis - E Lokes; A Franke; G Mayr; H ElAbd (Journal of Crohn's and Colitis, 2025)
Abstract Background The HLA region leads in the number of the strongest genetic associations for chronic immune-mediated diseases, including Inflammatory Bowel Disease1. Despite decades of research, the role of HLA in modulating chronic T cell-mediated responses remains unclear. HLA proteins present antigens for recognition by T cell receptors (TCRs). TCRs bear six complementarity determining regions (CDR), with the most variable CDR3 of the beta chain (CDR3b) due to a V(D)J recombination. The importance of CDR3 is determined by its direct interaction and recognition of antigens. Recent work by Ishigaki et al.2 identified that HLA-DRB1 site 13 influences the amino acid composition of CDR3b. Building on this, we extended the mapping between HLA sites and the CDR3b region to detect HLA sites that significantly contribute to the amino acid composition of CDR3b in IBD TCR repertoires. Methods We performed a comprehensive CDR3-QTL association analysis based on multivariate multiple linear regressions on a large dataset of ~2,000 paired HLA and TCR repertoires of healthy donors (n = 767) and IBD patients (n = 1188: 786 CD and 402 UC) using the analytical framework of Ishigaki et al.2 Results We discovered multiple novel HLA-DRB1 and HLA-DQ sites with distinct influences on TCRs. HLA-DRB1 sites 11 and 57 and DQB1 sites 57 and 71, located in antigen-binding pockets, strongly influence CDR3 composition in the IBD cohort. Notably, these effects were more pronounced in Crohn’s disease than in ulcerative colitis. HLA-DRB1 sites 67 and 73 and site 55 in DQB1 significantly influenced CDR3 composition only in healthy donors. HLA-DRB1 sites 13 and 71 and DQB1 site 87 were observed in both datasets, suggesting shared mechanisms irrespective of disease.The structural analysis revealed that healthy-specific sites directly interact with TCR, while common and IBD-specific sites predominantly occupy antigen-binding pockets. Conclusion Our study extensively identifies novel HLA sites that influence the most variable region in TCR - CDR3b in IBD patients. Our findings propose two distinct mechanisms by which HLA influences the CDR3: (1) direct TCR binding in TCRs (2) antigen-driven modulation in IBD-specific and common sites. The majority of identified HLA sites align with the loci previously associated with autoimmune diseases, and have been previously linked to common infections, particularly Epstein-Barr virus infection, suggesting that HLA influences CDR3 composition through both antigen-driven and direct TCR interactions. References 1.Goyette P, Boucher G, Mallon D, et al. High-density mapping of the MHC identifies a shared role for HLA-DRB1*01:03 in inflammatory bowel diseases and heterozygous advantage in ulcerative colitis. Nat Genet. 2015;47(2):172-179. doi:10.1038/ng.3176 2.Ishigaki K, Lagattuta KA, Luo Y, James EA, Buckner JH, Raychaudhuri S. HLA autoimmune risk alleles restrict the hypervariable region of T cell receptors. Nat Genet. 2022;54(4):393-402. doi:10.1038/s41588-022-01032-z 3.Matzaraki V, Kumar V, Wijmenga C, Zhernakova A. The MHC locus and genetic susceptibility to autoimmune and infectious diseases. Genome Biology. 2017;18(1):76. doi:10.1186/s13059-017-1207-1 4.Kachuri L, Francis SS, Morrison ML, et al. The landscape of host genetic factors involved in immune response to common viral infections. Genome Medicine. 2020;12(1):93. doi:10.1186/s13073-020-00790-x